Pengembangan Bahan Ajar Fisika SMP Berbasis STEM (Science, Technology, Engineering and Mathematics) Terintegrasi Karakter Pada Materi Usaha dan Pesawat Sederhana - Mahfuddin, Muhammad Fiqhi; Wahyuni, Siti (UPEJ Unnes Physics Education Journal, 2021)
Based on the observations, teaching materials used in junior high school 1, Padangan, Bojonegoro Regency in the form of BSE (Electronic School Book) curriculum 2013 revision, the STEM (Science, Technology, Engineering, and Mathematics) are less specific and not contain aspects of character development for students Therefore, this study aims to find out character, feasibility, legibility, and students’ responses towards physics teaching material based on STEM integrated character. The research method used mixed methods; it used sequential explanatory design, whereas there were two steps. The first step was conducted using a qualitative method, resulting in the teaching material plan product, and the second step was conducted using a quantitative method (experiment) to test the feasibility of the teaching material. The teaching material has characteristics based on STEM-integrated character. Based on the result analysis of the feasibility test, we obtained a value of 92.5%, which means that the teaching materials developed are in the very feasible category. Then, the legibility test results of 84.71%, which means that the teaching materials developed are easy to understand, and the results of students' responses to the teaching materials developed of 91.69%, which means that the developed teaching materials received a very good response.